2020
DOI: 10.1007/s41809-020-00068-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparing bilingual and monolingual performance on the attention network test: meta-analysis of a literature inspired by Albert Costa

Abstract: Are there differences between bilinguals and monolinguals in non-linguistic cognitive processes related to attention? Recent interest in this question, which has a long history, was stimulated by ideas presented in Bialystok's 2001 book: Bilingualism in development: Language, literacy, and cognition. Because attention is a multi-faceted construct Costa et al. (Cognition 106(1):59-86, 2008, Cognition 113(2):135-149, 2009) sought to answer this question using the attention network test (ANT), a simple-toadminist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…We expect to observe a positive association between degree of bilingualism and monitoring, consistent with domain general cognitive benefits of bilingualism (Bialystok & Craik, 2022). Additionally, we expect to observe a positive association between degree of bilingualism and executive control (Arora & Klein, 2020). Considering that the majority of past studies compare monolingual with bilingual samples and that bilingual language status is generally assessed through proficiency (Surrain & Luk, 2017), we expect that improved monitoring and executive control would be associated with higher levels of proficiency.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…We expect to observe a positive association between degree of bilingualism and monitoring, consistent with domain general cognitive benefits of bilingualism (Bialystok & Craik, 2022). Additionally, we expect to observe a positive association between degree of bilingualism and executive control (Arora & Klein, 2020). Considering that the majority of past studies compare monolingual with bilingual samples and that bilingual language status is generally assessed through proficiency (Surrain & Luk, 2017), we expect that improved monitoring and executive control would be associated with higher levels of proficiency.…”
Section: Introductionsupporting
confidence: 63%
“…Previous studies investigating bilingual effects on attention using the ANT have reported mixed findings. In their Bayesian meta-analysis, Arora and Klein (2020) identified credible evidence in support of reduced interference effects in young adult bilinguals, but no evidence for this outcome in children. Additionally, there was no credible evidence in support of bilinguals demonstrating a global reduction in RT across all trial types, nor increased efficiency in either alerting or orienting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for attentional disengagement, however, the idea that bilinguals would be advantaged in this particular type of monitoring is difficult to reconcile with the traditional executive attention framework. The main obstacle is that efficient monitoring of this type does not result in reduced congruency effects, the signature pattern of efficient executive attention (but see Arora & Klein, 2020; Grundy, 2020). Relatedly, traditional theories of cognitive control (e.g., Botvinick et al, 2001) assume that what is being monitored is conflict, not item type.…”
Section: Discussionmentioning
confidence: 99%